2020
DOI: 10.1123/ijspp.2018-0901
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Physiological Determinants of Rock Climbing

Abstract: Purpose: Rock climbing performance relies on many characteristics. Herein, the authors identified the physical and physiological determinants of peak performance in rock climbing across the range from lower grade to elite. Methods: Forty four male and 33 female climbers with onsight maximal climbing grades 5a–8a and 5a–7b+, respectively, were tested for physical, physiological, and psychological characteristics (independent variables) that were correlated and modeled by multiple regression and principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 23 publications
(47 reference statements)
0
48
0
3
Order By: Relevance
“…As such, rock climbing has been very popular among children, adolescents, and adults as a recreational and competitive sport [7]- [11]. As mentioned in the preceding section, It mostly leads to an increase in related disciplines, such as sport climbing, mountaineering, bouldering, big wall climbing, traditional, ice, and mixed climbing, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, rock climbing has been very popular among children, adolescents, and adults as a recreational and competitive sport [7]- [11]. As mentioned in the preceding section, It mostly leads to an increase in related disciplines, such as sport climbing, mountaineering, bouldering, big wall climbing, traditional, ice, and mixed climbing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and physiological factors, such as endurance and strength, determine optimal climbing performance, starting from the base level to the elite. However, optimum performance is achieved only in case one train continuously and with a lot of focus [7], [13], [14]. Besides, other factors such as psychological and mental strategy also affect the performance of rock climbing [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the above mentioned research indicate that the issue of the importance of flexibility in sport climbing still requires research. The latest research, carried out on a large sample (44 men and 33 women), by the MacKenzie et al [22], indicates gender-dependent gradation of the flexibility compounds (measured with non-specific and specific tests) with a change in sport climbing levels. Significant correlations were noted in the male group.…”
Section: Introductionmentioning
confidence: 99%
“…Significant correlations were noted in the male group. MacKenzie et al [22] concluded from the results of their research that flexibility belongs to the group of secondary determinants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation